Influence of vitamin B12 and folic acid on cognitive disorders in the elderly (Research, Society and Development, 2020)
In aging, some level of functional impairment is common as a consequence of health problems inherent to this phase of life. The literature demonstrates the importance of micronutrients for prevention or control of these diseases. In this context, vitamin B12 and folic acid (B9) are noteworthy, as their deficiency is associated with complications that may decrease the quality of life of this population. Therefore, the aim of the present study was to perform a review to describe important aspects related to the association between B12 and B9 in the cognitive health of the elderly. A total of 16 articles were used to compose the review, divided into 3 analysis categories that relate these micronutrients to the occurrence of Alzheimer's disease, loss of cognition and the presence of depression in the elderly. Low levels of B12 and B9 have been observed in Alzheimer's disease. Most articles related reduced vitamin levels with poor performance on cognitive performance, and finally, low concentrations of micronutrients were found in elderly with depression. Based on the above, it can be inferred that B12 and B9 deficiency is associated with increased homocysteine and methylmalonic acid concentrations that cause central nervous system alterations, especially resulting in depression and cognitive impairment, making it important to routinely evaluate the levels of these vitamins. in the elderly as they constitute a group of high vulnerability.